The Study of Poetry Anthology “Di Atas Viaduct”: A Portrait of a Changing Urban Society in Bandung, Indonesia - Yulianeta (South Asian Journal of Social Sciences and Humanities, 2023)
Purpose of the study: This research is based on the phenomenon of urban society in which the complexity of urban culture has caused the Indonesia to change. For example, the polluted Cikapundung river, the rarely heard of Sundanese songs, the rice fields turned into settlements, and the large number of prostitutions spread across Bandung, West Java, Indonesia. Methodology: This study aims to reveal the portrait of the urban society of Bandung in the poetry anthology. The method used in this study is the sociology of literature carried out with a sociological approach focusing on the analysis of the relationship between literature and humans. Main Findings: Based on the results, the poems show a portrait of urban society in Bandung, namely ecological damage, lifestyle transformation, individualization, prostitution, poverty, social inequality, and spatial segregation. The portrait of urban society is illustrated in the poetry anthology Di Atas Viaduct. Applications of this study: The results of this research can be used as a reflection of people’s lives through literary works.Novelty/Originality of this study: Therefore, the results show that the poet’s perspective on the changes in the city of Bandung brought by urban culture.